Montology: a mountain perspective on transdisciplinary research and sustainable development - Haller, Andreas (2020)
Mountain regions face decisive challenges, not only for their sustainable development but also fortheir very reproduction. These challenges have to do with the increasingly serious impact of climate and environmental change, the impact of socioeconomic and cultural globalization on mountain populations and the ecosystems they inhabit, and the effects of urbanization on mountain agriculture. Based on these premises, this article introduces the notion of “montology” by investigating, on the one hand, the historical development of the term and, on the other, by presenting the essential principles of a perspective committed to building a real transdisciplinarity in mountain studies. Finally, through the example of urbanization and its impact on Andean agriculture, we intend to highlight the need to adopt a montological perspective in order to contribute to the analysis of human environmental problems and to the sustainable development of the region.